Generating alternative fuel and bioplastics from medical plastic waste and waste frying oil using microwave co-pyrolysis combined with microbial fermentation. (January 2022) - Wan Mahari, Wan Adibah; Kee, Seng Hon; Foong, Shin Ying; Amelia, Tan Suet May; Bhubalan, Kesaven; Man, Mustafa; Yang, YaFeng; Ong, Hwai Chyuan; Vithanage, Meththika; Lam, Su Shiung; Sonne, Christian
Abstract: In the present study, microwave co-pyrolysis (MCP) was used to simultaneously convert medical plastic waste (MPW) and waste frying oil (WFO) into liquid oil products. The MCP process demonstrated a faster heating rate (24 °C/min) and shorter process time (20 min) compared to conventional pyrolysis techniques converting MPW and WFO into liquid oil (≥80 wt%). The MCP reduced the oxygen content from 25.7 to 9.82 wt% in liquid oil encompassing light aliphatic hydrocarbons ranging from C10 to C28, generating a novel sustainable liquid fuel. The liquid having a high carbon content (approximately 77.1 wt%) and low carbon to nitrogen ratio (27.9) is a suitable energy feedstock for polyhydroxyalkanoate (PHA) bioplastic production in the form of poly3-hydroxybutyrate [P(3HB)]. The liquid oil acted as an energy source for the growth of Bacillus sp. During microbial fermentation, yielding approximately 11% (w/w) P(3HB). Bioplastics are biodegradable, biocompatible with humans and non-toxic to marine organisms, representing a valuable additive in the production of cosmetics, detergents, and as medical scaffolds for tissue engineering. The results indicate the promising upcycling of waste products by this approach through pyrolytic biorefinery into value-added fuel and bioplastic products, being important for the future sustainable production of renewable resources. Graphical abstract: Image 1 Highlights: Medical plastic waste and waste frying oil are treated via microwave co-pyrolysis. The process shows fast heating rate (24 °C/min) and short process time (20 min). 81 wt% yield of C10 –C28 hydrocarbon liquid oil is obtained as promising fuel. The pyrolysis reduces oxygen content in the liquid oil from 25.7 to 9.8 wt%. The oil is a desirable energy source for microbial fermentation into bioplastics.